The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fnut.2018.00027
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Supplementation During Resistance Training Does Not Lead to Greater Bone Mineral Density in Older Humans: A Brief Meta-Analysis

Abstract: Creatine supplementation during resistance training has potential beneficial effects on properties of bone in aging adults. We systematically reviewed randomized controlled trials (RCTs) investigating the effect of creatine supplementation combined with resistance training on bone mineral density (BMD) in aging adults. We searched PubMed and SPORTDiscus databases and included RCTs of ≥3 months duration that examined the combined effect of creatine and resistance training on bone mineral in adults >50 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
1
18
0
3
Order By: Relevance
“…It's believed that creatine supplementation has an effect on the increase in the activity of skeletal muscles (14,15). It has been suggested that creatine supplementation and resistance training improve properties of body composition (16,17). One possible reason for the increased lean body mass following creatine supplementation and strength training may be due to the increase in the number of satellite cells and muscle nuclear density in human skeletal muscle fibers (18).…”
Section: Discussionmentioning
confidence: 99%
“…It's believed that creatine supplementation has an effect on the increase in the activity of skeletal muscles (14,15). It has been suggested that creatine supplementation and resistance training improve properties of body composition (16,17). One possible reason for the increased lean body mass following creatine supplementation and strength training may be due to the increase in the number of satellite cells and muscle nuclear density in human skeletal muscle fibers (18).…”
Section: Discussionmentioning
confidence: 99%
“…As with its effects on markers of bone turnover, the effect of creatine on bone mineral properties in aging adults is equivocal. A recent meta-analysis [71] assessed five studies regarding the effectiveness of creatine on bone [65,69,70,72,73]. These studies assessed 3–12 months of creatine supplementation (5–8 g/day) with a loading phase of about 20 g/day for 5 days in two of the studies [65,69], combined with resistance training (2–3 days/week) in males and females (57–85 years of age).…”
Section: Creatine and Aging Bonementioning
confidence: 99%
“…Apesar de termos sido capazes de subanalisar os dados de acordo com o nível de atividade física das participantes, nenhuma delas estava envolvida regularmente em um treinamento de força. No entanto, uma recente meta-análise mostrou que a suplementação de Cr em combinação ao treinamento de força não foi capaz de melhorar a DMO em idosos quando comparado ao treinamento de força isolado (Forbes et al, 2018). O efeito da suplementação de Cr juntamente com o treinamento de força a longo prazo (>12 meses) ainda precisa ser esclarecido.…”
Section: Discussionunclassified
“…(Somjen et al, 1994) e que a mesma, pode ser afetada por alguns fatores que já são conhecidos por modularem o metabolismo ósseo, como o IGF-1 (Sömjen e Kaye, 1994), a 1,25 di-hidroxivitamina D3 (Somjen et al, 1984), e o paratormônio (Somjen et al, 1985;Kaye et al, 1990). Além disso, como citado anteriormente, o tratamento com uma substância análoga a Cr provoca distúrbios na formação de osso endocondral tanto in vivo quanto in vitro (Funanage et al, 1992). Somado a isso, sabe-se que durante a osteoclastogênese ocorre aumento da atividade enzimática da CK cerebral e que a administração de um fármaco (ciclocreatina) capaz de inibir a sua atividade leva a supressão da reabsorção óssea e consequentemente da diferenciação dos osteoclastos in vitro, o que possivelmente pode afetar o turnover ósseo (Chang et al, 2008).…”
Section: Consumo Alimentarunclassified
See 1 more Smart Citation